2018
DOI: 10.1111/papr.12707
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cryoablation to Control Cancer Pain: A Systematic Review

Abstract: Cryoablation is effective in controlling cancer pain without relevant side effects. However, more studies are needed to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 40 publications
1
26
0
Order By: Relevance
“…Quality of life parameters were improved, and functional status was preserved through the 6 months of follow-up. These results support the findings of prior retrospective and prospective studies that have demonstrated cryoablation provides rapid and durable nonopioid pain relief and opiate reduction in patients with painful metastatic disease to the bone (14,16,(18)(19)(20)(21). Notably, these findings are in line with the largest reported prospective study that included 69 metastatic bone tumors from 61 patients who were treated with cryoablation, which found that the mean score for worst pain in the past 24-hour period, scored using the BPI-SF, decreased from 7.1 prior to cyroablation to 5.1 1 week after treatment to 1.4 at 24 weeks after treatment (P , .0001) (19).…”
Section: Discussionsupporting
confidence: 88%
“…Quality of life parameters were improved, and functional status was preserved through the 6 months of follow-up. These results support the findings of prior retrospective and prospective studies that have demonstrated cryoablation provides rapid and durable nonopioid pain relief and opiate reduction in patients with painful metastatic disease to the bone (14,16,(18)(19)(20)(21). Notably, these findings are in line with the largest reported prospective study that included 69 metastatic bone tumors from 61 patients who were treated with cryoablation, which found that the mean score for worst pain in the past 24-hour period, scored using the BPI-SF, decreased from 7.1 prior to cyroablation to 5.1 1 week after treatment to 1.4 at 24 weeks after treatment (P , .0001) (19).…”
Section: Discussionsupporting
confidence: 88%
“…In Denmark, surgical resection is still considered the preferred treatment of solitary metastatic RCC 3. This in line with cryoablation historically being favoured by the elderly and comorbid patients 10. Cases like this could be the beginning of a paradigm shift but recurrence and incomplete treatment are a concern.…”
Section: Discussionmentioning
confidence: 69%
“…The available evidence on cryoablation used as pain control is limited. But a recently published systematic review suggests that cryoablation is effective in controlling cancer pain, without relevant adverse effects 10…”
Section: Discussionmentioning
confidence: 99%
“…PCA has become an established treatment option in the management of a number of tumors, like renal or hepatocellular carcinomas, and for tumors of limited size, it can be considered as an alternative to surgery 17,18 . PCA is also frequently used for pain control, especially in the setting of advanced cancer 19,20 …”
Section: Introductionmentioning
confidence: 99%
“…17,18 PCA is also frequently used for pain control, especially in the setting of advanced cancer. 19,20 This retrospective analysis evaluated the outcome in all patients treated by PCA in our sarcoma center for unresectable sacral primary-or loco-regionally recurrent chordoma, with a minimal 5 years follow-up.…”
mentioning
confidence: 99%